The rise of the algorithmic child: protecting children in smart homes - Nash, V (Springer Wiesbaden, 2023)
Children’s Internet use is often presumed to consist only of popular entertainment activities such as scrolling through social media, playing games, or watching videos, all typically undertaken on personal devices, with Internet safety policy and practice targeted accordingly. But in reality, children’s Internet use is much more varied, including interactions with screenless smart devices in the home and via third party services outside the home. This chapter considers the practical and policy implications of such use, focusing on possible security and privacy risks as well as larger ethical questions about the datafication of childhood.